Facing "The Book" : investigating the discursive construction of Facebook through multiple modalities and the consequent construction of ideology. - Nortje, Daniela (My University, 2010)
This research sought to present Facebook from an alternative perspective, one not typically engaged with. Just as architecture, design and other modes have been identified as contributors to meaning, so too does their realisation in a virtual setting. The impact or importance of these modes is perhaps even more pronounced in virtual settings as they not only seek to communicate meaning but seek to establish a degree of rapport between reality and virtual domains. The principle aims of the research were to critically analyse the architecture of Facebook, paying specific attention to the discursive mechanisms and devices employed in maintaining its existing usership and communication of a central ideology; to assess the extent to which this particular ideology is reflected in the ‘physical’ or structural components of the site as well as to compare alternative modes of discourse such as the Facebook architecture and sections of text in order to establish the degree to which these are convergent or divergent from each other. Using a combination of Fairclough (2001) critical discourse analysis and an adaption of the multimodal discourse analysis Kress and van Leeuwen (2001) set out in their seminal work on the interdiscursivity of Discourse, Design, Production and Distribution. These methodologies were used to perform a multimodal discourse analysis of the Facebook architecture, ‘home’ page, ‘profile’ page and other key elements of the site. In addition to this, critical discourse analysis was used to analyse the ‘Facebook Principles’ and integrate them into a holistic and multimodal analysis of the contributions these modes had to the emergence of ideology. Drawing on the work of Baudrillard, on the key critics of consumer culture and technology, the research identified that Facebook provided a comprehensive representation of the various ways technology has impacted on forms of communication as a well as the way social relationships are mediated and constructed.